Pengaruh Pengelolaan Kelas terhadap Motivasi Belajar Siswa di MTs Al Mahrus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The purpose of this study was to determine how classroom management affects students' desire to learn at MTs Al Mahrus. This study uses a quantitative approach and an ex-post facto research design because the research variables arose naturally without the researcher's assistance. Students in grades VII, VIII, and IX at MT Al Mahrus were the subjects of this study. To obtain an overview of the learning conditions in the classroom, observations and questionnaires were used as supporting data. The results of the study indicate that classroom management at MT Al Mahrus is in the good category, while student learning motivation is in the uncertain category. The data obtained were analyzed using descriptive statistics and inferential statistics with the help of the SPSS program. The results of the descriptive test show that the level of classroom management and student learning motivation are in the good category. These results confirm that effective classroom management is very important for increasing students' desire to learn.